Peran Mazhab Fikih dalam Pembentukan Hukum Islam Klasik dan Modern - Anwar Habibi Siregar (Pusat Riset dan Inovasi Nasional, 2025)
The school of jurisprudence has a crucial role in the formation of Islamic law, both in the classical and modern eras. In the classical period, schools of thought such as Hanafi, Maliki, Syafi'i, and Hanbali became the main basis for formulating Islamic law through a structured ijtihad methodology. Each school of thought developed its own way of interpreting the Qur'an, Hadith, ijma', and qiyas, which then contributed to the diversity of Islamic law. In the modern era, the role of schools of jurisprudence remains relevant in responding to contemporary legal challenges, especially in economic, social, and technological issues. Islamic law reform in various Muslim countries often refers to the principles of these schools by adapting them to the national legal system. Therefore, the study of schools of jurisprudence not only contributes to the historical development of Islamic law but also serves as a foundation for formulating legal solutions that are adaptive to the dynamics of the times.